Papyri copticae magicae: Volume 1: Formularies = Coptic magical texts - Dosoo, Korshi; Preininger, Markéta (Archiv für Papyrusforschung und verwandte Gebiete Beiheft, 2023)
This volume is the first in a new series of editions of Coptic-language "magical" manuscripts from Egypt, written on papyrus, ostraca, parchment, and paper, and dating to between the fourth and twelfth centuries CE. Their texts attest to non-institutional rituals intended to bring about changes in the lives of those who used them – heal disease, curse enemies, bring about love or hatred, or see into the future. These manuscripts represent rich sources of information on daily life and lived religion of Egypt in the last centuries of Roman rule and the first centuries after the Arab conquest, giving us glimpses of the hopes and fears of people of this time, their conflicts and problems, and their vision of the human and superhuman worlds. This volume presents 37 new editions and descriptions of manuscripts, focusing on formularies or "handbooks", those texts containing instructions for the performance of rituals. Each of these is accompanied by a history of its acquisition, a material description, and presented with facing text and translations, tracings of accompanying images, and explanatory notes to aid in understanding the text